The Economic Impact of Climate Change on the Local Apple - Ariadi, Bambang Yudi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
An unavoidable climate change has an impact on agricultural production. This study aims at determining farmers’ knowledge concerning climate change and farmers’ behavior in apple cultivation, as well as it aims at investigating the impact of climate change on apple productivity, environmental damage, and apple prices. Primary data were collected using structured interviews to farmers of apple. Structural Equation Model (SEM) is employed to analyze the effect of climate change on production, environment and price changes. The results showed farmers possessed knowledge concerning climate change based on information mainly received from television and their perceived experience. Climate change causes the increase of warmer air temperatures, drought, and the need for product facilities, like fertilizers and pesticides. However, it causes the decrease of apple production. Climate change has a significant negative effect on apple productivity and the economic value of apples. The environment also has a negative effect on apple productivity at a lower level of significance. During climate change, apple productivity has a negative effect on apple prices, It means that the higher the apple productivity is, the lower the apple price will be. Hence, climate change caused the impact of a decrease in the economic value of local apple agribusiness in Malang Raya.